In Conversation with Professor Jacklyn Cock, Author of Maids and Madams - David du Toit (The Thinker)
David du Toit: Your book, Maids and Madams, is one of the seminal texts in domestic work literature in South Africa. What inspired you to write about domestic work during the apartheid era?